ANALISIS PELAKSANAAN FUNGSI MANAJEMEN OLEH PETUGAS AVIATION SECURITY (AVSEC) DI BANDAR UDARA INTERNASIONAL JUANDA SURABAYA - Salsabila Pharamita Magfiroh; Anita Nur Masyia’ah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Management functions consist of planning, organizing, directing, and controlling. The obstacle that the researchers found was that aviation security officers were confused when dealing with passengers carrying liquids in unlabeled bottles. Therefore aviation security officers need to have the ability to carry out management functions in carrying out their duties and responsibilities to maintain aviation security and safety. The purpose of this study was to determine the implementation of the management function by aviation security officers at Juanda International Airport, Surabaya and to find out the obstacles faced and find solutions in carrying out management functions by aviation security officers at Juanda International Airport, Surabaya. This study used a qualitative method. The research was conducted at Juanda International Airport in Surabaya which was held in May-June 2023. The data collection techniques used were observation, interviews and documentation. To test the validity of the data used by researchers, namely triangulation of sources and triangulation of techniques. Data analysis used is data reduction, data presentation, and conclusions. The results of the study show that aviation security officers carry out management functions including: (1) planning (planning) including objectives, duties and responsibilities of aviation security officers; (2) organizing (organizing) includes human resources, division of tasks, facilities and infrastructure; (3) directing includes communication, development, and guidance; (4) supervision (controlling) includes direct supervision and provision of motivation. The obstacles faced include the lack of aviation security officers at Juanda International Airport in Surabaya, aviation security officers who lack updates regarding the latest SOPs, aviation security officers face the character of passengers. While the solution is that several tasks can be handled by one aviation security officer in multiple ways, refreshing and the supervisor providing information regarding the latest SOP, providing the latest information to passengers.